Biomechanical regulation of sportsmen external breath characteristics with use of pneumo-vibration effect - Dychko, B.; Kochergin, A. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Its known strength development and «stamina» of respiratory muscles improve at their training or exercising. When this happens, almost all vital functional systems of a person (cardiovascular, neuromuscular, immune, blood circulatory, etc.) improve, and respiratory muscles develop without changes in kinematical and dynamic structures of the movement performed. Sporting practice shows that low frequency (12 - 30 Hz) muscles "vibrostimulation" increases their (muscles) efficiency. The exerciser using of pneumavibration load for respiratory muscles in exhalation of breathing is offered. We underline that «combined» exerciser`s effect is very important for sport so that it wouldn`t interfere with your technique. In this case training effect significantly increase. The purpose of this study was an experimental research was carried out for the exerciser`s effect to sportsmen external respiration.